2016
DOI: 10.1108/ssmt-10-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical reliability of solder joints in PCBs assembled in surface mount technology

Abstract: Purpose – The purpose of this paper is to determine the dependence of mechanical strength of solder joints on printed circuit boards from the soldering process parameters and operating conditions of the electronic device. Design/methodology/approach – The research was performed using the Taguchi method of planning of experiments. Evaluation of the quality of solder joints was made on the basis of microscopic observations, X-ray analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Voids in the joint reduce the mechanical strength and conductivity of a joint. It follows that the reduction of voids is beneficial and, in fact, often necessary (Wassink, 1989;Borgesen et al, 2012;Lee et al, 2013;Borecki and Serzysko, 2016). Intermetallic compounds (IMC), especially the occurrence of IMCs and IMC layer thickness, are also important properties affecting the reliability of a solder joint.…”
Section: Introductionmentioning
confidence: 99%
“…Voids in the joint reduce the mechanical strength and conductivity of a joint. It follows that the reduction of voids is beneficial and, in fact, often necessary (Wassink, 1989;Borgesen et al, 2012;Lee et al, 2013;Borecki and Serzysko, 2016). Intermetallic compounds (IMC), especially the occurrence of IMCs and IMC layer thickness, are also important properties affecting the reliability of a solder joint.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some scholars have conducted research on the relationship between assembly process parameters and the shear and tensile strengths of welded joints. Shi Kai [3] studied the effect of laser power, laser action time, nitrogen pressure and welding height and other process parameters on the shear strength of welded joints during laser ball implantation based on the polar difference analysis, the results show that the laser ball implantation process parameters on the shear strength of welded joints in descending order of laser power, nitrogen pressure, laser action time, welding height; Janusz Borecki [4] et al analyzed the relationship between the welding process parameters and the mechanical strength of the welded joint, assessed the weld quality of the welded joint through the weld joint shear and clarified the damage mechanism of the welded joint under shear; Ou Wenkun [5] designed the corresponding welding experiments and welded joint tensile test experiments according to the process window to investigate the effect of laser power, heating time and nitrogen pressure on the mechanical properties of the welded joint law. Found that the laser power and heating time on the mechanical properties of welded joints, the nitrogen pressure on the mechanical properties of welded joints is less affected; Yao, L. et al [6] tested and compared the mechanical properties of QFP solder joints formed at different laser output powers and showed that the semiconductor laser output power directly affects the tensile strength of QFP solder joints at the same braze composition; Bingwei Shen [7] studied the effect of welding time (1 to 9 min) and welding temperature (210 to 290°C) on the microstructure and mechanical properties of welded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Surface mount technology (SMT) has become the key process of printed circuit board assembly (Huang et al , 2011). Important steps in the manufacturing process include: stencil printing, coating the solder paste on the bonding pad on the PCB, and using automated equipment to precisely place the parts on the PCB (Lau et al , 2016; Borecki and Serzysko, 2016; Huang and Huang, 2014). Next, reflow soldering is carried out.…”
Section: Introductionmentioning
confidence: 99%